Crecimiento económico y el desempleo en la región Loreto en el periodo 2007 – 2021 - Tapullima Mori, Samanta Lucas (2024)
This thesis analyzes the relationship between economic growth and unemployment in the Loreto region, Peru, during the period 2007-2021. It was found that Loreto's economy grew at an average year-on-year rate of 2.10%, driven by economic diversification and reduced dependence on the oil extraction sector. The average Gross Domestic Product (GDP) for the period was 8,140 million soles. The average unemployment rate was 2.99%, with a decreasing trend, showing that economic growth contributes to the reduction of unemployment. Statistical analyses, including the Shapiro-Wilk normality test and Pearson correlation coefficient, confirmed an inverse and significant relationship (-74.13%) between economic growth and unemployment. This implies that, as Loreto's real GDP increases, the unemployment rate decreases. These findings are consistent with economic theories that posit that robust economic growth increases demand for labor and reduces unemployment. The conclusions suggest that economic diversification is key to sustained growth and reduced unemployment. It is recommended to continue with diversification, invest in infrastructure and job training, and implement active employment policies. These measures can help maintain economic stability and improve working conditions in Loreto.